The influence of CuO nanoparticles and boron wastes on the properties of cement mortar - Yildirim, M.; Derun, E. M. (CONSEJO SUPERIOR INVESTIGACIONES CIENTIFICAS-CSIC, 2018)
In this study, compressive and flexural strength, thermal properties, and pore structure of mortars modified with two types of boron waste and different amounts of CuO nanoparticles were investigated. The binders were prepared with 3% of borogypsum or borax waste and nano-CuO at concentration up to 4%. The setting time, compressive and flexural strength at 3, 7, and 28 days, DTA/TG, XRD, BET, and water absorption tests were carried out, and optimal nano-CuO percentages were determined. It was observed that nano-CuO addition in the range 2%-2.5% can improve mechanical properties, reduce the amount of unreacted portlandite, increase water absorption resistance, and decrease the setting time for borogypsum-containing mortars. The optimum nano-CuO replacement ratio changes between 0.5%-1% for borax waste-containing mortars. The results showed that nano-CuO was able to promote hydration reactions, act as a nanofiller, and provide a kernel for nucleation reactions.
Keywords: Compressive strength; Mortar; Thermal analysis; Waste treatment; X-ray diffraction; FLY-ASH; NANO-ALUMINA; BOTTOM ASH; NANO-FE2O3 POWDERS; THERMAL-PROPERTIES; ORE WASTE; SILICA; CONCRETE; MICROSTRUCTURE; Construction & Building Technology; Materials Science